Penerapan Algoritma Genetika untuk Sistem Penjadawalan Kuliah - Akhmad Qashlim; Muhammad Assiddiq (JURNAL ILMU KOMPUTER, 2016)
Timetables problems arise because of some work done simultaneously, while its resources are limited, a scheduling problem can occur in scheduling sporting events, programs converensi, scheduling in educational institutions, the scheduling of railways, as well as the scheduling of the colleges that have complexity a very big problem that arises because the number of students, faculty and lecture meetings that should be done at the same time very much but constrained in the limited space and time. This resulted in a clash in the classroom, faculty, and students. Completion of this problem requires techniques and computational methods for optimum results. This study proposes a method for the genetic algorithm timetable system at the university. a case study conducted at the faculty of computer science, University of Al Asyariah Mandar. System testing has been done by combining hard and soft constraint constraint resulted in scheduling courses are created automatically and solutions that do not conflict with the schedule of preparation time schedule relatively faster. Scheduling information system can developet with web-based applications and other optimization methods.